World’s main science-technology trends for last ten years and next ten years - Chi, Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
During the last ten years the world’s science-technology passed new trends such as enhancement of roles of fundamental research and social sciences and humanities, development of high techs, considerable contribution of science-technology for economic development, promotion of science-technology activities in enterprises, internationalization of science-technology activities, etc. They remain the main directions of science-technology during the next ten years with some deepening and extending adjustments of the previously established trends. Code: 12082001